Characterisation of drag and wake properties of canopy patches immersed in turbulent boundary layers. (31st May 2016) - Taddei, S.; Manes, C.; Ganapathisubramani, B.
Abstract : The wakes and the drag forces of canopy patches with different densities, immersed in turbulent boundary layers, are investigated experimentally. The patches are circular (with outer diameter D ) and are made of several identical circular cylinders (height, H, and diameter, d ). The bulk aspect ratio of all of the patches ( AR=H/D ) was fixed at 1 and the patch density ( φ=N_cd^2/D^2, also referred to as the solidity) is altered by varying the number of cylinders ( N_c ) in the patch. Drag measurements show that the patch drag coefficient increases with increasing density. However, the drag coefficient of the highest investigated density ( φ≈ 0.25 ) is greater than the drag coefficient of a solid patch (i.e. φ=1, which is a solid cylinder with AR=1 ). Particle image velocimetry (PIV) measurements were carried out along the streamwise–wall-normal ( x – y ) plane along the centreline of patch and in the streamwise–spanwise ( x – z ) plane at its mid height (i.e. y=H/2 ). Mean velocity fields show that the porosity of the patch promotes bleeding along all directions. It was observed that bleeding along the vertical/horizontal direction increases/decreases with increasing φ . Furthermore, it was also observed that bleeding along the lateral direction dictates the point of flow separation along the sides of the patch and makes it independent of φ . All of these aspects make wakes for porous patches markedly different from their solid counterpart and provide a rational basis to explain the observed trends in the drag coefficient.